Science Integrated Learning Model to Enhance The Scientific Work Independence of Student Teacher in Indigenous Knowledge Transformation - Parmin, P.; Sajidan, S.; Ashadi, A.; Sutikno, S.; Fibriana, F. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The scientific work independence is the core competency of student teacher of science. In this research, the effectiveness of the Science Integrated Learning Model (SIL) was measured in term of the scientific work independence of student teacher of science in changing the societyâ€™s original knowledge into scientific knowledge. The changing was measured through Ethnoscience learning. The experimental method was used with the control group and experimental group in three different universities. The result of the t-test shows a correlation coefficient significance value at 0.000 < 0.05. Therefore, it concludes that there is not any difference between the experimental and control group. However, there is an effect of model application on the independence of the scientific work of student teacher of science.Â Â